International Transfers of Managers in North American and European MNEs - Ondrack, Daniel (Journal of International Business Studies, 1985)
Global-scale MNEs require a network of managers to direct and control operations around the world. Managerial resources for these jobs can be managers from the headquarters country, host and third countries. International transfers can be for specific staffing needs, for management development and for organization development. The general hypothesis examined in this paper was the global scale MNEs would operate in a regio-or geocentric fashion with full integration of the world pool of managerial resources for all international transfers. Case studies were done on two North American and two European MNEs in the chemicals and electronics industries. World-wide transfers and consequent career opportunities were found in all cases for managers from headquarters countries. Regional transfers and careers were possible for host and third-country managers in regio-centric MNEs, but only national careers were possible in a poly-centric MNE. Temporary transfers to world or regional headquarters for management development were found for host and third-country managers, but transfers for organization development were for headquarters nationals. No consistent differences in uses of transfers or international careers were found between North American and European MNEs.